2021
DOI: 10.1111/ijfs.15162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of enzyme treatment of rice bran on gamma‐aminobutyric acid synthesis by Lacto bacillus

Abstract: Gamma‐aminobutyric acid (GABA) is a major inhibitory neurotransmitter in the central nervous system. The production GABA from the cheaper glutamic acid is a valuable process. Rice bran is a potential source of glutamic acid decarboxylase which was therefore selected for production of gamma‐aminobutyric acid (GABA) using lactic acid bacteria (Lactobacillus brevis (Lb.brevis) VTCC‐B397). The influences of treatment of defatted rice bran with α‐amylase, Alcalase (Al), Flavourzyme (Fl) and their combinations at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Meanwhile, the application of ultrafiltration was shown to be effective for GABA recovery (9.5 g/L) from the fermentation broth of rice bran extract (Lai & Pham, 2020). Moreover, it was found that rice bran was defatted before treatment of enzyme (α‐amylase) could enhance GABA formation up to 6.4 g/L in the L. brevis ‐fermented solution (Lai et al, 2021). Therefore, the application of recovery techniques as well as pre‐processing of rice bran before fermented by Lactobacillus can improve amount of GABA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the application of ultrafiltration was shown to be effective for GABA recovery (9.5 g/L) from the fermentation broth of rice bran extract (Lai & Pham, 2020). Moreover, it was found that rice bran was defatted before treatment of enzyme (α‐amylase) could enhance GABA formation up to 6.4 g/L in the L. brevis ‐fermented solution (Lai et al, 2021). Therefore, the application of recovery techniques as well as pre‐processing of rice bran before fermented by Lactobacillus can improve amount of GABA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that rice bran was defatted before treatment of enzyme (α-amylase) could enhance GABA formation up to 6.4 g/L in the L. brevis-fermented solution (Lai et al, 2021).…”
Section: Gaba Content In Gepmentioning
confidence: 99%
“…Then, the mixture was filtrated by cloth to collect defatted rice bran extract. The suspension was further heated for sterilisation at 121 °C for 20 min (Lai et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The fermented conditions were 30 °C of temperature, pH 5.0 for 48 h in flask. Following fermentation, the media were sterilised at 121 °C for 10 min to inactivate bacteria (Lai et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation